2018
DOI: 10.1039/c7sc04249c
|View full text |Cite
|
Sign up to set email alerts
|

Beyond optical rotation: what's left is not always right in total synthesis

Abstract: Longstanding debate on the absolute configuration of frondosin B was definitively solved using circular dichroism spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
1
12
1
Order By: Relevance
“…The compounds in this sample did present additional conformational flexibility, due to the fused cyclohexene and cycloheptadiene rings that can obtain several energetically favorable conformations; these were previously described in greater detail. 35 Additionally, the methyl ether group can adopt two configurations that are planar with the phenyl ring it is connected to. Crucially for the MRR analysis, one of these two configurations of OMe-frondosin B 5 results in a strong molecular dipole moment (>2 Debye), while the other has very low dipole moment (<0.3 Debye).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The compounds in this sample did present additional conformational flexibility, due to the fused cyclohexene and cycloheptadiene rings that can obtain several energetically favorable conformations; these were previously described in greater detail. 35 Additionally, the methyl ether group can adopt two configurations that are planar with the phenyl ring it is connected to. Crucially for the MRR analysis, one of these two configurations of OMe-frondosin B 5 results in a strong molecular dipole moment (>2 Debye), while the other has very low dipole moment (<0.3 Debye).…”
Section: Resultsmentioning
confidence: 99%
“…As the regioisomeric byproduct 6 contains two chiral centers, in the previous study of this reaction 35 the relative stereochemistry was determined on the basis of 1 H ROESY 2-D NMR experiments on an isolated sample with comparison to chemical shifts predicted using DFT. Just as for regioisomers, MRR is extremely precise in distinguishing between diastereomers on the basis of their differences in moments of inertia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in OR obtained for products of distinct synthetic routes had been attributed to an unexpected inversion of the C-8 stereogenic center. However, a recent report by Joyce et al [ 33 ] demonstrated that the presence of a minor impurity (ca. 7%), that appears in a key step late in the synthesis, was responsible for measured OR values of opposite signs for the synthetic products with the same AC.…”
Section: Introductionmentioning
confidence: 99%
“…7%), that appears in a key step late in the synthesis, was responsible for measured OR values of opposite signs for the synthetic products with the same AC. As a result, the assignment of the absolute stereochemistry of the natural product was also compromised [ 33 ]. The authors finally state that the reported inversions of the AC assigned at C-8 came “ only from differences observed in the measurements of a small optical rotation conducted on minute quantities of material, often of unknown chemical or enantiopurity ”.…”
Section: Introductionmentioning
confidence: 99%